Role of toys in the development of healthy infants - Mikołajewska, Emilia; Komendziński, Tomasz; Dreszer, Joanna; Bałaj, Bibianna; Mikołajewski, Dariusz (Journal of Education, Health and Sport, 2015)
Mikołajewska Emilia, Komendziński Tomasz, Dreszer Joanna, Bałaj Bibianna, Mikołajewski Dariusz. Role of toys in the development of healthy infants. Journal of Education, Health and Sport. 2015;5(4):219-223. ISSN 2391-8306. DOI: 10.5281/zenodo.16845 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%284%29%3A219-223 https://pbn.nauka.gov.pl/works/554832 http://dx.doi.org/10.5281/zenodo.16845 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.02.2015. Revised 27.03.2015. Accepted: 10.04.2015. Role of toys in the development of healthy infants Emilia Mikołajewska1,2,3, Tomasz Komendziński3,4, Joanna Dreszer3,4, Bibianna Bałaj3,4, Dariusz Mikołajewski3,5,6 1 Department of Physiotherapy, Ludwik Rydygier Collegium Medium in Bydgoszcz, Nicolaus Copernicus University in Toruń 2 Rehabilitation Clinic, The 10th Clinical Military Hospital with Policlinic, Bydgoszcz, Poland 3 Neurocognitive Laboratory, Interdisciplinary Center for Modern Technologies, Nicolaus Copernicus University in Toruń 4 Department of Cognitive Science, Nicolaus Copernicus University, Toruń, Poland 5 Institute of Mechanics and Applied Computer Sciences, Kazimierz Wielki Universit, Bydgoszcz, Poland 6 Department of Informatics, Nicolaus Copernicus University, Toruń, Poland Corresponding author: Emilia Mikołajewska Rehabilitation Clinic Military Clinical Hospital No. 10 and Polyclinic Bydgoszcz, Poland e-mail: e.mikolajewska@wp.pl, emiliam@cm.umk.pl www: http://emikolajewska.netstrefa.eu Keywords: rehabilitation; development; gesture; toy use; parent–child interaction; Abstract Developmental outcomes in infants can be significantly improved thanks to promising use of approapriate toys. Objective assessment of their positive influence to functional achievements in healthy infants may completely change attitude to new generation of toys, developing motor, cognitive, and social skills. Despite advances in toys assessment their true influence remains incomplete. This study aims at assessment how current knowledge and experience influences principles of the toys selection and use in healthy infants.